Patient‐specific structural connectivity informs outcomes of responsive neurostimulation for temporal lobe epilepsy. Issue 8 (4th June 2022) - Charlebois, Chantel M.; Anderson, Daria Nesterovich; Johnson, Kara A.; Philip, Brian J.; Davis, Tyler S.; Newman, Blake J.; Peters, Angela Y.; Arain, Amir M.; Dorval, Alan D.; Rolston, John D.; Butson, Christopher R.
Abstract: Objective: Responsive neurostimulation is an effective therapy for patients with refractory mesial temporal lobe epilepsy. However, clinical outcomes are variable, few patients become seizure‐free, and the optimal stimulation location is currently undefined. The aim of this study was to quantify responsive neurostimulation in the mesial temporal lobe, identify stimulation‐dependent networks associated with seizure reduction, and determine if stimulation location or stimulation‐dependent networks inform outcomes. Methods: We modeled patient‐specific volumes of tissue activated and created probabilistic stimulation maps of local regions of stimulation across a retrospective cohort of 22 patients with mesial temporal lobe epilepsy. We then mapped the network stimulation effects by seeding tractography from the volume of tissue activated with both patient‐specific and normative diffusion‐weighted imaging. We identified networks associated with seizure reduction across patients using the patient‐specific tractography maps and then predicted seizure reduction across the cohort. Results: Patient‐specific stimulation‐dependent connectivity was correlated with responsive neurostimulation effectiveness after cross‐validation ( p  = .03); however, normative connectivity derived from healthy subjects was not ( p  = .44). Increased connectivity from the volume of tissue activated to the medial prefrontal cortex, cingulate cortex, and precuneus was associated with greater seizure reduction. Significance: Overall, our results suggest that the therapeutic effect of responsive neurostimulation may be mediated by specific networks connected to the volume of tissue activated. In addition, patient‐specific tractography was required to identify structural networks correlated with outcomes. It is therefore likely that altered connectivity in patients with epilepsy may be associated with the therapeutic effect and that utilizing patient‐specific imaging could be important for future studies. The structural networks identified here may be utilized to target stimulation in the mesial temporal lobe and to improve seizure reduction for patients treated with responsive neurostimulation.